SocietyÔÇÖs Perception on The Quality of Public Services and The Discourse on The Splitting of Nagari Manggopoh Agam - Sarmen Aris; Bustamin Bustamin; Yulia Ningsih; Oktri Permata Lani; Raihanah Abdullah (Alfuad: Jurnal Sosial Keagamaan, 2023)
This study aims to determine the public's perception of the quality of public services in Nagari Manggopoh and to determine the public's perception of the discourse on the division of Jorong in Nagari Manggopoh. This research uses a descriptive quantitative method. Respondents came from the Nagari Manggopoh community a research data collection using questionnaires and field observations. Data were analyzed using technique analysis percentage descriptive. The study results show that people's perceptions of the quality of public services in Nagari Manggopoh showed very good and good, reaching 88%. Meanwhile, the community's perception of the village management discourse (Jorong Splitting) in Nagari Manggopoh shows a very high percentage, reaching 93%. This study concluded that public services provided by Nagari Manggopoh occupy an excellent interval value. Meanwhile, the discourse on village arrangement (addition of Jorong) received enthusiastic support from the Nagari Manggopoh Community.